1997
DOI: 10.1046/j.1365-3156.1997.d01-210.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting high‐risk years for malaria in Colombia using parameters of El Niño Southern Oscillation

Abstract: SummaryT h e interannual variation in malaria cases in Colombia between ~9 6 0 and 1992 shows a close association with a periodic climatic phenomenon known as El Niiio Southern Oscillation (ENSO).Compared with other years, malaria cases increased by ~7 . 3 % ) during a Nirio year and by 35.1% in the post-Niiio year. T h e annual total number of malaria cases is also strongly correlated ( Y = 0.62, P < 0.001) with sea surface temperature (SST) anomalies in the eastern equatorial Pacific, a principal parameter o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
70
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(74 citation statements)
references
References 8 publications
2
70
0
2
Order By: Relevance
“…20 El Niño events represent the best analog for the impacts of increased frequency of extreme weather events. A number of studies have documented an increased incidence of malaria associated with El Niño events, [20][21][22][23][24][25] but evidence for dengue-ENSO (El Niño Southern Oscillation) associations is equivocal. 26 Extreme weather events are also likely to facilitate the spread of dengue by disrupting water supply, sewerage and sanitation services.…”
mentioning
confidence: 99%
“…20 El Niño events represent the best analog for the impacts of increased frequency of extreme weather events. A number of studies have documented an increased incidence of malaria associated with El Niño events, [20][21][22][23][24][25] but evidence for dengue-ENSO (El Niño Southern Oscillation) associations is equivocal. 26 Extreme weather events are also likely to facilitate the spread of dengue by disrupting water supply, sewerage and sanitation services.…”
mentioning
confidence: 99%
“…The impacts of global and local environmental change on infectious disease has been understood mainly in terms of population density and the distribution of pathogens and their vectors 1 24 34 . For example, temporal increases in malaria incidence in Rwanda 22 and Colombia 4 have been associated with the effects of periodic El Niño events and overall surface warming on vector thermosensitivity. No studies have been conducted on the interaction of chemical pollutants and the epidemiology of infectious disease.…”
mentioning
confidence: 99%
“…Even though malaria is a highly complex multifactorial disease, previous studies have identified a significant association between the increase in the number of malaria cases in Colombia during the occurrence of El Niño (15)(16)(17)(18)(19). Such studies have focused on a nationwide level at yearly timescales, whereas no effort has been made to identify the El Niño malaria association at a local level in the endemic regions of rural Colombia at monthly timescales.…”
mentioning
confidence: 99%